Investigation of Flow Through Centrifugal Pump Impellers Using Computational Fluid Dynamics - Weidong Zhou; Zhimei Zhao; T. S. Lee; S. H. Winoto (International Journal of Rotating Machinery)
With the aid of computational fluid dynamics, the complex internal flows in water pump impellers can be well predicted, thus facilitating the design of pumps. This article describes the three-dimensional simulation of internal flow in three different types of centrifugal pumps (one pump has four straight blades and the other two have six twisted blades). A commercial three-dimensional Navier-Stokes code called CFX, with a standard k–ε two-equation turbulence model was used to simulate the problem under examination. In the calculation, the finite-volume method and an unstructured grid system were used for the solution procedure of the discretized governing equations for this problem.